Fast, scalable and secure over-the-air bootstrap of Linux operating systems with Wi-Fi ad hoc networks - Zúquete, André (2020)
This article describes and evaluates the performance of DETIboot, a system conceived for securely deploying temporary Linux systems into countless receiving hosts close enough to a Wi-Fi DETIboot server. This system was created with the ultimate goal of installing, in numerous students’ laptops and just-in-time, special Linux distributions for being temporarily used in practical classes. In this document we present an overview of DETIboot, a comprehensive description of the coding used in the broadcast communication and a detailed performance evaluation in a spacious auditorium. This evaluation did not involve security features to reduce the amount of variables influencing the final results. However, previous experiments allow us to extrapolate a maximum of 5% increase in the download time due to security. On average, it took us 50.1 s to download a 225 MiB Slax Linux over 802.11g, taking on average 15% more time than the theoretical lower bound of our setup (43.4 s). The influence of the position of receivers in the auditorium was not prominent.